Sustained Swimming Training Is Associated With Reversible Filet Texture Changes of European Sea Bass (Dicentrarchus labrax L.) - Shi, C.; Wang, J.; Yang, Z.; Gao, X.; Liu, Y.; Wang, C. (Frontiers in Physiology, 2019)
This study investigated the effect of training and detraining on growth, chemical composition, white muscle fibres and fillet texture of the European sea bass (Dicentrarchus labrax L.). Fish were divided into the control and training group, which were subjected to water velocities of 0.2 and 1.0 body length per second (bl s−1, respectively, for 32 d (phase Ⅰ). Then, half of the fish in the training group were randomly selected and detrained at a velocity of 0.2 bl s-1 for another 32 d (detraining group), while the velocity of the rest fish in training group (1 bl s-1) and control group (0.2 bl s-1) remained unchanged (phase Ⅱ). The results showed that the growth, body composition and white muscle fibre densities of the control and trained fish were not significantly different in either phase. Training significantly altered the muscle fibre distribution (P < 0.05), and the training group had fewer 80-90 μm fibres than the control and detraining group at the end of the experiment (P < 0.05). The training group also had significantly higher values of white fibre muscle textural parameters (hardness, adhesiveness, cohesiveness, springiness, gumminess and chewiness) in phase I (P < 0.05), and these parameters were significantly correlated with pH (P < 0.05). However, these differences in texture and the correlation weakened when the fish were detrained in phase Ⅱ. These results indicate that increase in muscle pH after training may alter the flesh texture characteristics of sea bass, and that sustained swimming could induce a reversible change in the fillet texture of sea bass.